2008
DOI: 10.5794/jjoms.54.413
|View full text |Cite
|
Sign up to set email alerts
|

Surgical intervention of osteonecrosis of the maxilla associated with bisphosphonate therapy: report of a case

Abstract: Bisphosphonate-related osteonecrosis of the jaws (BRONJ) has a major negative effect on the quality of life of patients. However, there is still no consensus on effective treatment strategies for BRONJ. We report a case of BRONJ that was treated surgically. A 57-year-old woman who was given a diagnosis of breast cancer with multiple metastasis was referred to our clinic for evaluation of swelling of the left upper gum. Clinical examination revealed a fistulous tract with pus discharge that had developed after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Good results have been reported with aggressive surgical treatment such as reconstructive surgery following mandible detachment when no neovascularization was present 12,13,28) . Furthermore, some studies from Japan 1,2,16,30) have reported that it is possible to control ONJ by aggressive surgery or prompt reconstructive surgery in breast cancer patients on BP drugs. They also note that mandible detachment of the area affected or up to its borders may be necessary in some cancer patients, as long as the general health condition otherwise allows.…”
Section: Discussionmentioning
confidence: 99%
“…Good results have been reported with aggressive surgical treatment such as reconstructive surgery following mandible detachment when no neovascularization was present 12,13,28) . Furthermore, some studies from Japan 1,2,16,30) have reported that it is possible to control ONJ by aggressive surgery or prompt reconstructive surgery in breast cancer patients on BP drugs. They also note that mandible detachment of the area affected or up to its borders may be necessary in some cancer patients, as long as the general health condition otherwise allows.…”
Section: Discussionmentioning
confidence: 99%
“…Critical surgical treatment taking lesion off clearly has been effective for the cases with separated sequestrum from peripheral bone obviously. [ 18 19 ] Free sequestrum should be removed without exposing normal bone. [ 20 ] In contrast, it is difficult to remove the direct factors of non-BRONJ cases such as radio-osteonecrosis or cryptogenic osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%